A preliminary study of green-house gases interference for ammonia sensing in the mid UV region - Hadi, Manap; Lewis, Elfed (IEEE, 2011)
This paper describes a preliminary study of the possibility for greenhouse interference during ammonia measurement in the 200 nm - 230 nm region. An absorption spectrum for ammonia was compared with the greenhouse gases absorption lines to theoretically justify that there were no discernible interference effects during the ammonia concentration measurements. It was theoretically found that the primary greenhouse gases namely ozone, methane and nitrous oxide have no significant interference for ammonia sensing in the 200 nm - 210 nm region.